The Polish labour market in transition - Viktor Steiner; Eugeniusz Kwiatkowski (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1995)
The paper presents an empirical analysis of labour force dynamics in Poland in the period 1992 - 1993. Transitions between employment, unemployment and non-participation in the labour force at the individual level are derived from panel data of the Polish Labour Force Survey. These transitions are related by means of a dynamic microeconometric model to various demographic and socio-economic characteristics of the labour force, labour market indicators and other structural variables. Based on estimated transition rates between all three labour force states and some simplifying assumptions we derive steady-state or 'equilibrium' unemployment rates for various groups of the labour force. It is shown that these differ greatly between demographic and socio-economic groups and how this is related to differences in the various transition rates between labour force states.
Keywords: 330